Electrolytic copper foil additive and preparation process of high-tensile warping-free 6-micron double-photoelectrolytic copper foil

By using specific additives in electrolytic copper foil to adjust the grain size and crystal plane orientation, the problems of insufficient tensile strength, excessive warping and high surface roughness in electrolytic copper foil in lithium-ion batteries are solved, and a high performance 6μm double-layer The preparation of photoelectrolytic copper foil improves the safety and charge and discharge performance of lithium-ion batteries.

CN119320967APending Publication Date: 2025-01-17SHAANXI FUTURE ADVANCED MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411451065.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing electrolytic copper foils have problems such as insufficient tensile strength, excessive warping and high surface roughness in lithium-ion battery applications, which affect the safety, cycle life and charge and discharge power of the battery.

Method used

The electrolytic copper foil additive consisting of grain refining agent DMPS, inhibitor DMBA, auxiliary accelerator MSAA and gloss improver 2-MBT was used to prepare high tensile strength and low curvature by adjusting the grain size and crystal plane orientation. A 6μm dual-photoelectrolytic copper foil with a curved and smooth surface.

Benefits of technology

The high tensile strength, low warpage and low surface roughness of the electrolytic copper foil are achieved, the uniformity of the coating of active substances in the negative electrode of the lithium-ion battery and the charging and discharge performance of the battery are improved, and the safety and energy density of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089139100000101
    Figure BDA0005089139100000101
  • Figure BDA0005089139100000111
    Figure BDA0005089139100000111
Patent Text Reader

Abstract

The invention provides an electrolytic copper foil additive and a preparation process of a high-tensile warping-free 6-micron double-photoelectrolytic copper foil, and belongs to the technical field of electrolytic copper foils. The additive is prepared by the following steps: respectively dissolving a grain refiner DMPS, an inhibitor DMBA, an auxiliary accelerator MSAA and a gloss improver 2-MBT in high-purity water to prepare four component solutions, and mixing the four component solutions. The invention relates to a preparation process of a 6-micron double-photoelectrolytic copper foil. The preparation process comprises the following steps: 1) dissolving a copper wire and sulfuric acid in the presence of pure air to obtain an acidic copper plating electrolyte base solution; (2) introducing the prepared additive mixed solution into an acidic copper plating electrolyte base solution, introducing into equipment for electrolyzing crude foil, and connecting direct current to obtain a copper foil; and (3) washing, stripping, rolling and drying the crude foil prepared in the step (2) to obtain a crude foil finished product. The electrolytic copper foil prepared by the method has the characteristics of high tensile strength and low warpage, the smooth surface and the rough surface have extremely low roughness, and the electrolytic copper foil shows relatively high glossiness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic copper foil, and in particular relates to an electrolytic copper foil additive and a preparation process of a high-tensile-resistance, warpage-free 6μm dual-photoelectrolytic copper foil. Background Art

[0002] The mechanical properties of lithium battery copper foil have a great impact on the safety, cycle life and charge and discharge power of lithium batteries. On the one hand, during the manufacturing process of the negative electrode of the lithium-ion battery, the copper foil will go through a roller drying process. On the other hand, during the operation of the battery, as lithium ions are embedded in and out of the negative electrode active material, the copper foil will be subjected to stress and deform.

[0003] The surface state and mechanical properties of lithium battery copper foil will determine the carrying capacity of the negative electrode active material and the bonding quality with the active material slurry. Specifically, if the roughness difference between the two sides of the copper foil is too large, it is easy to cause the negative electrode active material to break and delaminate, because of the difference in friction between the two sides. If the surface roughness is too high, it is easy to cause the formation of lithium dendrites when lithium ions are embedded. This is mainly because the high-roughness surface can provide few active sites, causing most of the lithium ions to deposit at the peaks of the copper foil to form dendrites. In severe cases, it pierces the separator inside the battery and causes a short circuit, threatening the safety of the battery. Similarly, the warping generated during the production of copper foil also has a great impact on the negative electrode coating process of downstream battery manufacturers. Excessive warping makes it impossible for the negative electrode to be evenly and smoothly coated on the copper foil.

[0004] Therefore, the smoothness and warping of both sides of the copper foil are also one of the test points for the selection of negative electrode current collector materials. In addition, the lithium battery industry's requirements for energy density force the rapid thinning of electrolytic copper foil, and some copper foil manufacturers have mass-produced 6μm electrolytic copper foil. However, the reduction in thickness also brings some difficulties, one of which is the reduction in the elongation of the copper foil, which directly leads to a decrease in the yield rate during the coating and transmission of the negative electrode roll-to-roll. There are also problems such as uniformity control and warping of the copper foil.

[0005] The electrolytic copper foil disclosed in Patent Document 1 (CN 103074657 B) has too high an additive concentration, which easily causes excessive inclusion of additives in the copper foil, substandard copper foil purity, reduced conductivity and other negative effects. Its mechanical properties can no longer meet current production requirements. The tensile strength requirement for high-grade lithium battery copper foil is already above 500 MPa, and the roughness value of its matte surface is too large, resulting in a large difference between the matte surface and the smooth surface, which is no longer suitable for the application of lithium batteries with better performance.

[0006] The surface roughness of the electrolytic copper foil disclosed in Patent Document 2 (CN 103649378 B) exceeds the standard, and some embodiments are even above 3.0 μm. Although it is theoretically beneficial to load more active substances, it is not conducive to the conductivity of the negative electrode of the battery because the smooth surface can provide more active sites. Secondly, the rough surface is not conducive to uniform coating of active substances, resulting in a decrease in the energy density and cycle life of the battery. In addition, the additive components selected do not care about the control of roughness.

[0007] In the non-patent literature (Yi Guangbin. Study on the microstructure and properties of electrolytic copper foil and its warpage mechanism [D]. Nanchang: School of Mechanical and Electrical Engineering, Nanchang University, 2014: 66-92), the relationship between the internal stress and texture of copper foil was studied, and it was proposed that the mechanism of the additive affecting the internal stress of copper foil is to refine the copper foil grains and promote the preferential growth of (220) texture. That is, by adjusting the crystal plane orientation distribution during the electrolysis of copper foil, the internal stress balance of copper foil is controlled, thereby suppressing warpage.

[0008] In the non-patent literature (Song Yan, Zhu Ruolin, Dai Zeyu, et al. Application of thiourea-like structure additives in the preparation of electrolytic copper foil [J]. Electroplating & Finishing, 2022, 41(17): 1245-1249.), the effect of thiourea-like structure additives on the mechanical properties of electrolytic copper foil was studied, and it was believed that it is very difficult to prepare a smooth and flat electrolytic copper foil surface using thiourea-like structures.

[0009] It can be seen from the above literature that the additives make the preferred orientation of the copper foil grains mainly (220). This kind of copper foil has a high tensile strength, but the warping caused by residual stress is large. The way to suppress warping is to increase the preferred orientation of the (111) crystal plane, because the appearance of the (111) crystal plane orientation proves that there is a considerable proportion of twin boundaries inside the copper foil, and the internal stress of the copper foil will be released by the twin boundaries. In addition, try to reduce the increase in grain size during the nucleation and growth of the copper foil, so that the stress on the smooth and rough surfaces of the copper foil is equivalent, and the residual stress is close to 0, and the copper foil will not warp. Neither of these two methods increases the grain size of the copper foil, nor sacrifices its mechanical properties, and the gloss and roughness of the copper foil surface are in excellent condition.

[0010] Based on the above, the present invention provides a new electrolytic copper foil additive from the perspective of additives, and uses this additive to provide an electrolytic copper foil preparation process. The additive is introduced under a reasonable electrolytic process to manufacture a 6μm electrolytic copper foil with both sides being bright and flat, having excellent tensile strength and extremely low warpage. Compared with the same type of double-sided smooth copper foil in the market, this electrolytic copper foil has the characteristics of high tensile strength and low warpage, and is very suitable for negative electrode current collector materials of lithium-ion batteries. Summary of the invention

[0011] Technical problem solved by the invention: In view of the problems existing in the prior art, the invention provides an electrolytic copper foil additive and a process for preparing a 6μm dual-photoelectrolytic copper foil with high tensile strength and no warping. By using the electrolytic copper foil additive provided by the invention, the prepared electrolytic copper foil has the characteristics of high tensile strength and low warping, and both the smooth and rough sides have extremely low roughness and present a high glossiness.

[0012] In order to achieve the above object, the technical solution adopted by the present invention is:

[0013] An electrolytic copper foil additive, wherein the additive is prepared by dissolving a grain refiner DMPS, an inhibitor DMBA, an auxiliary accelerator MSAA, and a gloss improver 2-MBT in high-purity water to prepare four component solutions, the four component solutions are mixed in an additive tank, and stirred evenly to prepare an additive mixed solution;

[0014] Among them, the mass concentration of the grain refiner DMPS solution is 0.1-10.0 mg / L, the mass concentration of the inhibitor DMBA solution is 0.1-10.0 mg / L, the mass concentration of the auxiliary accelerator MSAA solution is 0.1-20.0 mg / L, and the mass concentration of the gloss improver 2-MBT solution is 0.1-50.0 mg / L.

[0015] To further limit the above scheme, the grain refiner DMPS is sodium 2,3-dimercaptopropane sulfonate; the inhibitor DMBA is dihydroxymethylbutyric acid; the auxiliary accelerator MSAA is anilino methane sulfonic acid; and the gloss improver 2-MBT is 2-thiolbenzothiazole.

[0016] To further limit the above scheme, the mass concentration of the grain refiner DMPS solution is 2.0-6.0 mg / L, the mass concentration of the inhibitor DMBA solution is 1.0-5.0 mg / L, the mass concentration of the auxiliary accelerator MSAA solution is 3.0-13.0 mg / L, and the mass concentration of the gloss improver 2-MBT solution is 5.0-10.0 mg / L.

[0017] To further define the above scheme, the purity of the grain refiner DMPS is ≥99wt%, the purity of the inhibitor DMBA is ≥98wt%, the purity of the auxiliary accelerator MSAA is ≥98wt%, and the purity of the gloss improver 2-MBT is ≥98wt%.

[0018] A preparation process of a high-tensile and non-warping 6μm dual-photoelectrolytic copper foil comprises the following steps:

[0019] Step 1): Preparation of acid copper plating electrolyte base liquid: The acid copper plating electrolyte base liquid is prepared by dissolving copper wire with a purity of more than 99.96% and sulfuric acid of analytical purity or above in the presence of pure air; the electrolyte system must have a filtration system to improve purity, and cooperate with a heat exchange system to adjust the temperature;

[0020] Step 2): introducing the additive mixed solution prepared in any one of claims 1 to 4 into the acidic copper plating electrolyte base solution, and then passing it into the electrolytic foil equipment after the purification of the filtration system is completed, connecting direct current, and obtaining the original copper foil just electrodeposited, that is, the foil;

[0021] Step 3): The raw foil obtained in step 2 is washed, peeled, rolled up and dried to obtain a finished raw foil.

[0022] In the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 50-150 g / L, the mass concentration of sulfuric acid is 50-150 g / L, and the mass concentration of chloride ions is 1-50 mg / L;

[0023] The process parameters for electrolysis of the acid copper plating electrolyte base solution are: electrolyte temperature: 30-80°C, current density: 20-80A / dm 2 , electrolyte flow rate: 20~60m 3 / h, electroplating time: 1~10min.

[0024] Furthermore, in the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 80-105 g / L, the mass concentration of sulfuric acid is 80-110 g / L, and the mass concentration of chloride ions is 5-25 mg / L;

[0025] Furthermore, in the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 90±2 g / L, the mass concentration of sulfuric acid is 100±2 g / L, and the mass concentration of chloride ions is 15±0.2 mg / L.

[0026] Furthermore, in the above step 1), the process parameters for electrolysis of the acidic copper plating electrolyte base solution are: electrolyte temperature: 48-52°C, current density: 40-60A / dm 2 , electrolyte flow rate: 35-45m 3 / h, electroplating time: 1~3min.

[0027] Furthermore, in the above step 1), the process parameters for electrolysis of the acidic copper plating electrolyte base solution are: electrolyte temperature: 50±0.5°C, current density: 50A / dm 2 , electrolyte flow rate: 38±1m 3 / h, electroplating time: 1~3min.

[0028] The advantages of the present invention compared with the prior art are:

[0029] 1. This solution prepares an electrolytic copper foil additive suitable for high-performance lithium-ion batteries by adjusting the electrolyte additive without changing the electrolytic copper foil production equipment, and prepares the electrolytic copper foil preparation process by the additive. In the additive formula of the present invention, the grain refiner DMPS and the auxiliary accelerator MSAA are used to reduce the grain size in the copper ion electrodeposition process, so that the rough surface of the copper foil has a grain size and stress similar to the smooth surface, achieving high mechanical properties and inhibiting the warping of the copper foil. DMBA is used as an inhibitor to play a leveling role, while increasing the texture ratio of the (111) crystal plane and homogenizing the grain size, so that the residual stress of the copper foil is greatly reduced and the surface is bright and smooth. 2-Mercaptobenzothiazole (2-MBT) is used as an additive to improve gloss and has a certain leveling property, and is also a stress relief agent that can reduce the internal stress of the copper foil. The electrolytic copper foil prepared by the additive has extremely low surface roughness, high gloss and excellent mechanical properties. In the manufacturing process of lithium-ion batteries, the surface state of this electrolytic copper foil enables the negative electrode of the battery to carry more Si-C or C-type active materials, and the coating of the active materials is more uniform. In the use of the battery, the excellent mechanical properties and conductivity of this electrolytic copper foil further improve the charging and discharging power and safety;

[0030] 2. The additives provided in this scheme have a simple composition and are easy to control, and their components can all be purchased from the market. This not only reduces the raw material cost and management cost of copper foil production, but also contributes to the advancement of lithium battery technology and the expansion of the new energy market, ultimately bringing economic growth. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] First, this embodiment provides an additive for electrolytic copper foil, the components of the additive include sodium 2,3-dimercaptopropanesulfonate (DMPS), dimethylolbutyric acid (DMBA), anilino methanesulfonic acid (MSAA) and 2-thiolbenzothiazole (2-MBT).

[0033] In a preferred embodiment, the purity of sodium 2,3-dimercaptopropanesulfonate (DMPS) is ≥99wt%, the purity of dimethylolbutyric acid (DMBA) is ≥98wt%, the purity of anilino methanesulfonic acid (MSAA) is ≥98wt%, and the purity of 2-mercaptobenzothiazole (2-MBT) is ≥98wt%.

[0034] Sodium 2,3-dimercaptopropane sulfonate (DMPS) is a grain refiner, which is an additive that increases the tensile strength of copper foil by refining the grains. When it is added to 2.0-6.0 mg / L, the expected effect can be achieved. When the DMPS content is higher than 6.0 mg / L, the coating will produce white fog. When the DMPS content is lower than 2.0 mg / L, the brightness decreases and burrs may appear.

[0035] Dimethylolbutyric acid (DMBA) is an inhibitor that plays a leveling role. It increases the texture ratio of the (111) crystal plane and homogenizes the grain size, which greatly reduces the residual stress of the copper foil and makes the surface bright and smooth. When it is added to 1.0-5.0 mg / L, the expected effect can be achieved. When the DMBA content is higher than 5.0 mg / L, the tensile strength decreases. When the GMS content is lower than 1.0 mg / L, DMBA has little effect on the physical properties of the copper foil.

[0036] Methanesulfonic Acid Aniline (MSAA) is an auxiliary accelerator used in combination with 2-mercaptobenzothiazole (2-MBT). By refining the grains, the coating is smooth and the internal crystals are dense. When it is added to 3.0-13.0 mg / L, the expected effect can be achieved. When the MSAA content is higher than 13.0 mg / L, the copper foil becomes more brittle, the brightness decreases, and the elongation is significantly reduced. When the MSAA content is lower than 3.0 mg / L, the graininess of the rough surface of the copper foil increases.

[0037] 2-Mercaptobenzothiazole (2-MBT) is added as an additive to improve glossiness and has a certain leveling property. It is also a stress reliever that can reduce the internal stress of copper foil. When it is added to 5.0-10.0 mg / L, the expected effect can be achieved. When the 2-MBT content is higher than 10.0 mg / L, the glossiness decreases and turns white. When the 2-MBT content is lower than 5.0 mg / L, the warping caused by the internal stress of the copper foil cannot be effectively reduced.

[0038] The above four additives are dissolved in high-purity water to form four component solutions, which are then temperature-adjusted and mixed to form a mixed solution. The concentrations of the components are maintained at 2.0-6.0 mg / L of sodium 2,3-dimercaptopropane sulfonate (DMPS), 1.0-5.0 mg / L of dimethylolbutyric acid (DMBA), 3.0-13.0 mg / L of anilino methanesulfonic acid (MSAA) and 5.0-10.0 mg / L of 2-thiolbenzothiazole (2-MBT).

[0039] According to the prior art, additives make the preferred orientation of copper foil grains mainly (220). This copper foil has high tensile strength, but the warping caused by residual stress is large. The way to suppress warping is to increase the preferred orientation of the (111) crystal plane, because the appearance of the (111) crystal plane orientation proves that there are a considerable proportion of twin boundaries inside the copper foil, and the internal stress of the copper foil will be released by the twin boundaries. In addition, try to reduce the increase in grain size during the nucleation and growth of the copper foil, so that the stress on the smooth and rough surfaces of the copper foil is equivalent, and the residual stress is close to 0, and the copper foil will not warp. Neither of these two methods increases the grain size of the copper foil, nor sacrifices its mechanical properties, and the gloss and roughness of the copper foil surface are in excellent condition.

[0040] In the additive formula of the present embodiment, the grain refiner DMPS and the auxiliary accelerator MSAA are used to reduce the grain size during the copper ion electrodeposition process, so that the rough surface of the copper foil has a grain size and stress similar to that of the smooth surface, achieving high mechanical properties and inhibiting the warping of the copper foil. DMBA is used as an inhibitor to play a leveling role, while increasing the texture ratio of the (111) crystal plane and uniformizing the grain size, so that the residual stress of the copper foil is greatly reduced and the surface is bright and smooth. 2-Mercaptobenzothiazole (2-MBT) is used as an additive to improve glossiness and has a certain leveling property, and is also a stress relief agent that can reduce the internal stress of the copper foil.

[0041] Through the above technical scheme, the technical objectives that can be achieved by the present invention are as follows:

[0042] The roughness of the matte surface of the 6μm copper foil is Rz≤1.57μm, 280≤glossiness (Gs(60°))≤352; the tensile strength at room temperature and pressure after heat treatment is ≥553MPa, the elongation is ≥4.1%, and the warpage is less than 3.5mm.

[0043] Secondly, this embodiment provides a process for preparing a 6μm double-electrolytic copper foil with high tensile strength and no warping, comprising the following steps:

[0044] Step 1): Preparation of acidic copper plating electrolyte base solution: The acidic copper plating electrolyte base solution is prepared by dissolving copper wire and sulfuric acid in the presence of pure air;

[0045] Step 2): introducing the additive mixed solution prepared in any one of claims 1 to 4 into the acidic copper plating electrolyte base solution, and then passing it into the electrolytic foil raw equipment after the purification of the filtration system is completed, connecting direct current, and obtaining the original copper foil just electrodeposited, that is, the raw foil,

[0046] Step 3): The raw foil obtained in step 2 is washed, peeled, rolled up and dried to obtain a finished raw foil.

[0047] In the above step 1), the mass concentration of copper ions in the electrolyte is 80-105 g / L, the mass concentration of sulfuric acid is 80-110 g / L, and the mass concentration of chloride ions is 5-25 mg / L.

[0048] In a preferred embodiment, the mass concentration of copper ions in the electrolyte base solution is 90±2 g / L, the mass concentration of sulfuric acid is 100±2 g / L, and the mass concentration of chloride ions is 15±0.2 mg / L.

[0049] In the above step 1), the process parameters for electrolysis of the acid copper plating electrolyte base solution are: electrolyte temperature: 48-52°C, current density: 40-60A / dm 2 , electrolyte flow rate: 35-45m 3 / h, electroplating time: 1~3min.

[0050] In a preferred embodiment, the electrolysis process parameters are: electrolyte temperature: 50±0.5°C, current density: 50A / dm 2 , electrolyte flow rate: 38±1m 3 / h, electroplating time: 1~3min.

[0051] The technical solution of the present invention is described below by comparing the specific embodiments of the present invention with the comparative examples.

[0052] Examples 1-5 and Comparative Examples 1-4:

[0053] The mass concentration of copper ions in the electrolyte base liquid is controlled to be 90±2 g / L, the mass concentration of sulfuric acid is controlled to be 100±2 g / L, and the mass concentration of chloride ions is controlled to be 15±0.2 mg / L.

[0054] The electrolysis process parameters implemented are: electrolyte temperature: 50±0.5℃, current density: 50A / dm 2 , electrolyte flow rate: 38±1m 3 / h, electroplating time: 1~3min.

[0055] The raw foil with a thickness of 6 μm was prepared by electrolysis.

[0056] The following table (Table 1) shows the control parameters of the additives in Examples 1-5 and Comparative Examples 1-4:

[0057]

[0058] 1. Use a roughness meter to measure the Rz value at three locations of the sample and take the arithmetic mean of the results.

[0059] 2. Tensile strength (MPa) and elongation (%): The tensile strength (MPa) and elongation (%) of the copper foil before heat treatment were measured at room temperature and pressure using a tensile testing machine (Model 1122 manufactured by Instron) with reference to IPC-TM-650.

[0060] 3. Glossiness (Gs(60°)): The glossiness Gs(60°) of the matte surface of each electrolytic copper foil of Examples 1-4 and Comparative Examples 1-4 was measured using an LS192 gloss meter at a 60° emission and reception angle. The samples were placed on a flat surface, and measurements were taken and recorded at 5 different positions of each sample. The results were taken as the arithmetic average of all the data of each sample.

[0061] 4. Take 3 samples horizontally on the copper foil, place them horizontally on a plane, measure the height of the highest point, and calculate the average of the 3 data as the warpage (mm).

[0062] The test results are shown in the following table (Table 2):

[0063]

[0064] It can be seen from the physical properties of copper foil shown in Table 2:

[0065] The thickness of the electrolytic copper foil used as an example is kept at 6 μm, the surface roughness is kept below 1.57 μm, and the glossiness (Gs (60°)) is 280-352, which will allow the active materials on both sides of the negative electrode to adhere sufficiently and will not be delaminated due to being too smooth. At the same time, the appropriate glossiness also allows the adsorption and desorption of lithium ions on both sides of the negative electrode to be synchronized, thereby improving the charge and discharge cycle life and performance of the battery.

[0066] The room temperature tensile strength after heat treatment is 550MPa~650MPa, the elongation is ≥4.1, and the warpage is ≤3.5mm, which shows that the copper foil can still maintain high tensile strength and elongation under low warpage, so that the negative electrode plate can obtain a higher compaction density, effectively reducing the thickness of the plate, thereby improving the energy density of the lithium-ion battery.

[0067] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0068] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An electrolytic copper foil additive, characterized in that: The additive is prepared by dissolving a grain refiner DMPS, an inhibitor DMBA, an auxiliary accelerator MSAA and a gloss improver 2-MBT in high-purity water to prepare four component solutions, and then mixing the four component solutions evenly to prepare an additive mixed solution; Among them, the mass concentration of the grain refiner DMPS solution is 0.1-10.0 mg / L, the mass concentration of the inhibitor DMBA solution is 0.1-10.0 mg / L, the mass concentration of the auxiliary accelerator MSAA solution is 0.1-20.0 mg / L, and the mass concentration of the gloss improver 2-MBT solution is 0.1-50.0 mg / L.

2. The electrolytic copper foil additive according to claim 1, characterized in that: The grain refiner DMPS is sodium 2,3-dimercaptopropane sulfonate; the inhibitor DMBA is dihydroxymethylbutyric acid; the auxiliary accelerator MSAA is anilino methane sulfonic acid; and the gloss improver 2-MBT is 2-thiolbenzothiazole.

3. The electrolytic copper foil additive according to claim 1, characterized in that: The mass concentration of the grain refiner DMPS solution is 2.0-6.0 mg / L, the mass concentration of the inhibitor DMBA solution is 1.0-5.0 mg / L, the mass concentration of the auxiliary accelerator MSAA solution is 3.0-13.0 mg / L, and the mass concentration of the gloss improver 2-MBT solution is 5.0-10.0 mg / L.

4. The electrolytic copper foil additive according to claim 1, characterized in that: The purity of the grain refiner DMPS is ≥99wt%, the purity of the inhibitor DMBA is ≥98wt%, the purity of the auxiliary accelerator MSAA is ≥98wt%, and the purity of the gloss improver 2-MBT is ≥98wt%.

5. A process for preparing a 6μm double-electrochemical copper foil with high tensile strength and no warping, characterized in that: The following steps are involved: Step 1): Preparation of acidic copper plating electrolyte base solution: The acidic copper plating electrolyte base solution is prepared by dissolving copper wire and sulfuric acid in the presence of pure air; Step 2): introducing the additive mixed solution prepared in any one of claims 1 to 4 into the acidic copper plating electrolyte base solution, and then passing it into the electrolytic foil equipment after the purification of the filtration system is completed, connecting direct current, and obtaining the original copper foil just electrodeposited, that is, the foil; Step 3): The raw foil obtained in step 2 is washed, peeled, rolled up and dried to obtain a finished raw foil.

6. The process for preparing a high tensile strength and warpage-free 6μm dual-electrochemical copper foil according to claim 5, characterized in that: In the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 50-150 g / L, the mass concentration of sulfuric acid is 50-150 g / L, and the mass concentration of chloride ions is 1-50 mg / L; The process parameters for electrolysis of the acid copper plating electrolyte base solution are: electrolyte temperature: 30-80°C, current density: 20-80A / dm 2 , electrolyte flow rate: 20~60m 3 / h, electroplating time: 1~10min.

7. The process for preparing a high tensile strength and warpage-free 6 μm dual-electrochemical copper foil according to claim 6, characterized in that: In the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 80-105 g / L, the mass concentration of sulfuric acid is 80-110 g / L, and the mass concentration of chloride ions is 5-25 mg / L.

8. The process for preparing a high tensile strength and warpage-free 6μm dual-electrochemical copper foil according to claim 7, characterized in that: In the above step 1), the mass concentration of copper ions in the acidic copper plating electrolyte base solution is 90±2 g / L, the mass concentration of sulfuric acid is 100±2 g / L, and the mass concentration of chloride ions is 15±0.2 mg / L.

9. The process for preparing a high tensile strength and warpage-free 6 μm dual-electrochemical copper foil according to claim 6, characterized in that: In the above step 1), the process parameters for electrolysis of the acid copper plating electrolyte base solution are: electrolyte temperature: 48-52°C, current density: 40-60A / dm 2 , electrolyte flow rate: 35-45m 3 / h, electroplating time: 1~3min.

10. The process for preparing a high tensile strength and warpage-free 6μm dual-electrochemical copper foil according to claim 9, characterized in that: In the above step 1), the process parameters for electrolysis of the acid copper plating electrolyte base solution are: electrolyte temperature: 50±0.5°C, current density: 50A / dm 2 , electrolyte flow rate: 38±1m 3 / h, electroplating time: 1~3min.

Citation Information

Patent Citations

  • An additive for electrolytic copper foil and a production process for 7μm dual-light lithium-ion batteries.

    CN103074657B

  • Electrolytic copper foil, a method for manufacturing the electrolytic copper foil, and a lithium-ion secondary battery using the electrolytic copper foil as a current collector.

    CN103649378B